Inhibition of BET bromodomain attenuates angiotensin II induced abdominal aortic aneurysm in ApoE−/− mice. (15th November 2016) - Duan, Qiong; Mao, Xiaoxiao; Liao, Chaonan; Zhou, Haoyang; Sun, Zelin; Deng, Xu; Hu, Qiuning; Qi, Jun; Zhang, Guogang; Huang, He; Plutzky, Jorge; Yang, Tianlun
Abstract: Background: Excessive degradation of extracellular matrix by matrix metalloproteinases (MMP) is the major pathological feature of abdominal aortic aneurysm (AAA). Suppression of extracellular matrix degradation attenuates AAA initiation and progression in preclinical models. In the present study, we wanted to test the effect of JQ1, a small chemical molecule that selectively targets bromodomain and extra-terminal domain (BET), on AngII induced AAA formation in ApoE −/− mice. Methods and results: To study the role of BET bromodomain in AAA pathogenesis, male ApoE −/− mice were infused with angiotensin II (AngII, 1000 ng/kg/min) for 21 days and cotreated with JQ1 (50 mg/kg daily) or vehicle control (DMSO). In the in vitro study, we determined the mRNA expression of MMP genes by qPCR and their activity both by the kit and gelatin zymography assay. BET bromodomain inhibition resulted in decreased abdominal aortic diameter ( P < 0.05) measured by in vivo vascular ultrasound and ex vivo pathologic assessment of aortas. In pursuit of mechanisms for this effect on AAA, we observed that JQ1 treatment led to a downregulation of metalloproteinase gene expression and enzymatic activity both in vitro and in vivo. Conclusions: BET bromodomain inhibition improved AAA pathological sequelae, and this effect might be achieved though suppression of MMP genes expression and their activity.